The Yajña Chakra in Sujana human education - Yuliani, Ni Made; Rahayu , Ni Wayan Sri (Life and Death: Journal of Eschatology, 2024)
Education in Indonesia is always in the public spotlight, usually during the period of cabinet changes. Particularly, the Minister of National Education, who is always concerned with new policies along with new curriculum, which has an effect on parents and students as well as the wider community. Indonesia's human development index in 2022 reached 72.91, an increase of 0.62 points (0.86 percent) compared to the previous year (72.29). In terms of determining the development index, education is one of the keys. In this article, qualitative research examines the Yajña Chakra Concept in Sujana Human Education efforts. The data in this research was obtained through observation, literature study, interviews and Focus Group Discussions (FGD) related to the research theme and studied using content analysis. According to the Vedas, the philosophical background of education is to improve the quality of life of "manava" (humankind) and their lives to become "madhava", for instance human beings who have gentleness, compassion and high wisdom or wisdom. Whereas "manava" falls into "danava-danava", such as humans with giant characters, greed, envy and various other bad traits. Clearly, education is a continuous process in a 'linear' system, and has an important role in people's lives, which occurs in all social settings, not just at school. People gain insight, knowledge, and skills from others that they can use in their lives. Bali in particular, if Hindus truly realise the teachings of Yajña, especially Manusa Yajña, gaps in education should be addressed. Presently, Yajña is understood as a ritual ceremony and there seems to be a tendency to get bigger each day and seem increasingly difficult to carry out. Manusa Yajña should also make sacrifices for fellow humans, including advancing the world of education.